P2Y12 inhibitors with oral anticoagulation for percutaneous coronary intervention with atrial fibrillation: a systematic review and meta-analysis. Issue 8 (7th February 2020) - Lupercio, Florentino; Giancaterino, Shaun; Villablanca, Pedro Arturo; Han, Frederick; Hoffmayer, Kurt; Ho, Gordon; Raissi, Farshad; Krummen, David; Birgersdotter-Green, Ulrika; Feld, Gregory; Reeves, Ryan; Mahmud, Ehtisham; et al.
Abstract : Objective: This study aimed to compare the safety and efficacy of third-generation P2Y12 inhibitors versus clopidogrel in combination with oral anticoagulation (OAC) with or without aspirin in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI). Methods: We performed a systematic review including both prospective and retrospective studies that compared dual and triple antithrombotic regimens for bleeding and major adverse cardiac events (MACE) in patients with AF undergoing PCI. We analysed rates of bleeding and MACE by P2Y12 inhibitor choice. Risk ratio (RR) 95% CIs were measured using the Mantel-Haenszel method. Where study heterogeneity was low (I 2 <25%), we used the fixed effects model, otherwise the random effects model was used. Results: A total of 22 014 patients were analysed from the seven studies included. Among patients treated with both OAC and P2Y12 inhibitor with or without aspirin, 90% (n=9708) were treated with clopidogrel, 8% (n=830) with ticagrelor, and 2% (n=191) with prasugrel. When compared with clopidogrel, use of ticagrelor (RR 1.36; 95% CI 1.18 to 1.57) and prasugrel (RR 2.11; 95% CI 1.34 to 3.30) were associated with increased rates of bleeding. Compared with clopidogrel, there were no significant differences in rates of MACE with ticagrelor (RR 1.03; 95% CI 0.65 to 1.62) or prasugrel (RR 1.49; 95% CI 0.69 to 3.24). Conclusion: Based on this meta-analysis, the use of clopidogrel is associated with a lower rate of bleeding compared with ticagrelor or prasugrel in patients with AF on OAC undergoing PCI.